Impacts of the COVID-19 pandemic on supervised consumption service delivery in Vancouver and Surrey, Canada from the perspective of service providers - Tyson Singh Kelsall; Michelle Olding; Tara Myketiak; Nitasha Puri; Kanna Hayashi; Thomas Kerr; Mary Clare Kennedy (Discover Public Health)
Abstract Following the onset of the COVID-19 pandemic, an ever-increasing number of people have died from the toxic drug supply in Canada. Emerging evidence suggests that reduced access to harm reduction services has been a contributing factor. However, the precise impacts of the pandemic on supervised consumption service (SCS) delivery have not been well characterized. The present study sought to explore the impacts of the pandemic on SCS delivery in Vancouver and Surrey, Canada. Between October 2021 and March 2022, in-depth, semi-structured interviews were conducted with staff from two SCS: SafePoint in Surrey (n = 12) and Insite in Vancouver (n = 9). Thematic analysis focused on key changes to SCS delivery after the emergence of the COVID-19 pandemic, with a focus on associated challenges and emergent staff responses. Participants described key challenges as: capacity restrictions hindering service access and compromising care quality; exclusion of frontline staff perspectives from evolving SCS policy and practice decision-making; intensified power dynamics between staff and service users; and modified overdose response procedures, combined with a rise in complex overdose presentations, undermining service accessibility and quality. Emergent staff responses to these challenges included: collective staff organizing for changes to policy; individual frontline staff non-compliance with emerging policies; and staff experiencing burnout in their roles. This study highlights how COVID-19-related changes to service delivery produced challenges for SCS staff and service users, while identifying strategies employed by staff to address these challenges. Additionally, the findings point to opportunities to improve care for people who use drugs during intersecting public health crises.